If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + 6) = 36 Reorder the terms: 3(6 + y) = 36 (6 * 3 + y * 3) = 36 (18 + 3y) = 36 Solving 18 + 3y = 36 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 3y = 36 + -18 Combine like terms: 18 + -18 = 0 0 + 3y = 36 + -18 3y = 36 + -18 Combine like terms: 36 + -18 = 18 3y = 18 Divide each side by '3'. y = 6 Simplifying y = 6
| 18=3(r+12) | | (8n-6p)(7n-10p)= | | 3x^3-x^2-36x+12=0 | | 6(2x^2-7x-30)=0 | | 9m-m+3=-2(m+1) | | 21=11-6a | | 7.2=h+5.4 | | 6(2x^2-17x-30)=0 | | 5z+-8z+-12=9 | | 3b-2+2=1 | | g+11/20=3/4 | | 8s-8s+s=11 | | -14-6(2x+1)=16 | | 2+4x=3x | | 15x^2-4x+7=0 | | -9=f+14 | | B+7.3=8.4 | | 4+2(m+3)=22 | | T-5.8=6.9 | | k^2+2k-9=0 | | 55=5a | | K+19=-12 | | F-23=15 | | 220-5=250-10x | | (1-2x)*(1-2x)=2.4x | | 10y=4 | | 10-3(2x-4)=-14 | | 3(2+n)=66 | | x^2+4x+-32=0 | | x^2+34x+437=0 | | 2(3+n)=28 | | 4x^2+1.6x+1=0 |